Application of eutectic solvents in chemical and enzymatic reactions of upstream processes for biodiesel production / Shahidah Nusailah Rashid - Shahidah Nusailah , Rashid (2019)
This study introduces novel deep eutectic solvents (DESs) that act as catalyst in esterification of palm oil and media for enzymatic hydrolysis to produce palmitic acid. The conventional organic solvent will have to be a substitute in the near future by DES due to the economic viability and environmental concerns. The development of DES-based solvent and catalysis is at an exponential rate. Acidic crude palm oil (ACPO) with 9.2 % of free fatty acid (FFA) generated from industrial palm oil was pre- treated (esterified) before utilizing it as feedstock for biodiesel production. The pre-treatment of ACPO was conducted using (1R)-(-)-camphor-10-sulfonic acid (10-CSA) with choline chloride (ChCl); CSA-ChCl-ES and p-toluenesulfonic acid monohydrate (PTSA) mixed with benzyltrimethylammonium chloride (BAC); BAC-DES as the novel DES-based catalysts to remove the FFA to less than 2% at optimized condition. The optimal reaction conditions for CSA-ChCl-ES were 2.5 wt% of catalyst dosage, 10:1 molar ratio, 60 ⁰C of reaction temperature and 40 minutes of reaction time. While the reaction conditions for BAC-DES were 2 % catalyst dosage, 10:1 molar ratio of methanol to oil, 30 min of reaction time and reaction temperature of 60 °C gives high conversion and yield of 90 %. In the second part of this study, hydrolysis reaction of DES with lipase enzyme was investigated. The results show that DES is able to activate and stabilize lipases enzyme in hydrolysis reaction. DESs of the aqueous glycerol solution (GLY 85) as the hydrogen bond donor (HBD) with methyltriphenylphosphonium bromide (MTPB) and ChCl as salt was applied as new reagents media for enzymatic hydrolysis. The physicochemical properties such as viscosity, conductivity, density, surface tension, and freezing point were measured to establish DES characteristics. The results showed that DES at a ratio of 1:3 of ChCl-based DES and 1:5 of MTPB-based DES has their eutectic points at 213.4 K and 255.8 K respectively. The enzymatic activity of porcine pancreas and Rhizopus niveus lipases in DESs were examined. Both lipases were stable iv in all ratios of the DES especially in 80% concentration of DES. Overall, phosphonium-based DES showed higher activation towards porcine pancreas lipase (7.2 fold) compared to Rhizopus niveus lipase (0.9 fold) under the same conditions. To the best of our knowledge, this is the first time that aqueous glycerol was used to prepare DESs and subsequently applied for enzyme-based processes. Overall, these results proved that DES especially ChCl-based DESs could replace conventional solvents as they possess enormous potential; especially in the electrochemical technology given their values are higher than average conductivities. They also demonstrated a stabilizing effect on lipases in which the activity was stimulated in the presence of DESs in aqueous solution system. This feature could assist in transesterification in biodiesel synthesis.